THE INFLUENCE OF WORKLOAD ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION WITH TRANSFORMATIONAL LEADERSHIP AS A MODERATING VARIABLE AT THE REGIONAL REVENUE MANAGEMENT AGENCY OF BURU REGENCY - Yasmin Yulianti Mony; Priyastiwi Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the effect of workload on employee performance with job satisfaction as a mediating variable and transformational leadership as a moderating variable at the Regional Revenue Management Agency (BPPD) of Buru Regency. This study is motivated by the still low achievement of employee performance as indicated by fluctuations in performance realization and the failure to achieve regional revenue targets, which are thought to be influenced by high workload, low job satisfaction, and the less than optimal implementation of transformational leadership. This study uses a quantitative approach. The study population was all 42 employees of BPPD Buru Regency, and all were sampled using a saturated sampling technique. Data collection was carried out through a questionnaire using a Likert scale. Data analysis was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method using SmartPLS software version 4.0. The results of the study indicate that: (1) workload has a negative and significant effect on employee performance; (2) workload has a negative and significant effect on job satisfaction; (3) job satisfaction has a positive and significant effect on employee performance; (4) job satisfaction is proven to mediate the effect of workload on employee performance; and (5) transformational leadership moderates the influence of workload on job satisfaction positively, thereby weakening the negative impact of workload on job satisfaction. The findings of this study confirm that proportional workload management, increasing employee job satisfaction, and the effective implementation of transformational leadership are important factors in improving employee performance at the BPPD of Buru Regency.